PEMANFAATAN CANDI SINGOSARI SEBAGAI MEDIA PEMBELAJARAN BERBASIS KEARIFAN LOKAL PADA MATERI HINDU-BUDDHA DALAM MATA PELAJARAN IPS SMPN 20 KOTA MALANG - Satriyani, Deny Yaniar; Syarifuddin Arif; Kristiwi Estuningsih; Yusuf Agung Bintoro (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to describe the utilization of Singosari Temple as a learning medium based on local wisdom in the topic of Hindu-Buddhist civilization within the Social Studies subject at SMPN 20 Kota Malang. The background of this research lies in the need for contextual and meaningful teaching approaches to enhance students’ understanding and interest in history, particularly regarding Hindu-Buddhist cultural heritage. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The research subjects consisted of Social Studies teachers, seventh-grade students, and the principal of SMPN 20 Kota Malang. The results show that integrating Singosari Temple into Social Studies learning enhances students’ comprehension of historical concepts, fosters appreciation for cultural heritage, and shapes student character in terms of environmental and cultural awareness. The use of historical sites as instructional media effectively strengthens the connection between classroom content and real-life experiences. Thus, utilizing local wisdom such as Singosari Temple serves as a strategic alternative in developing contextual, student-centered, and character-oriented learning models in Social Studies.